An analysis of working capital management in Indiasan urgent need to refocus - Najib H. S. Farhan; Fozi Ali Belhaj; Waleed M. Al-ahdal; Faozi A. Almaqtari (Cogent Business & Management, 2021)
The current study aims to evaluate the impact of working capital components on the financial performance of Indian pharmaceutical companies. Moreover, it aims to analyze working capital among small, medium and large firms. The study uses a panel data of 82 pharmaceutical companies for the period from 2008 to 2017. Generalized Method of Moment (GMM) model is used for estimating the results. Findings show that there is a significant difference in managing working capital among small, medium and large firms. Furthermore, it is found that number of days' collection period, number of days' payable period and number of days' inventory holding period positively impact the financial performance of Indian pharmaceutical companies measured by return on assets and net operating margin. Whereas, cash conversion cycle has a negative impact on return on assets, net operating margin and Tobin's Q.
Keywords: 650; Working capital; financial performance; Pharmaceutical industry; GMM estimation